Peningkatan Nilai Ekonomi Komoditas Jamur Melalui Optimalisasi Cafe Edukasi dan Produk Kreatif di CV. Caca Jamur - Abraham Ismail Pulungan; Nelfita Rizka S. Depari; Emma Fadhilah; Candra Sigalingging; Riani Sari Sembiring; Lily Novianty; Kenaya Ade Revani; Haykal Brema (Universitas Nahdlatul Ulama Sumatera Utara, 2025)
This activity aimed to enhance the economic value of oyster mushroom commodities through the optimization of an educational cafe and the development of creative mushroom-based products at CV Caca Jamur, Pancur Batu District, Deli Serdang Regency. The main challenges faced by the partner included limited product innovation, conventional marketing practices, and the underutilization of the educational café as a medium for education, branding, and market expansion. The program was implemented using a participatory and collaborative approach by actively involving the partner in all stages of the activities, including problem identification, training and mentoring on product diversification, optimization of the educational café, strengthening of branding and packaging, and digital marketing assistance. The results demonstrated an improvement in the partner’s knowledge and skills in managing mushroom-based enterprises, the creation of diversified value-added mushroom products, and increased attractiveness of the educational café as a learning and promotional platform. Furthermore, the program contributed to broader market reach and increased income potential for the partner enterprise. This activity is expected to serve as a sustainable empowerment model for horticultural-based MSMEs through the integration of education, product innovation, and creative economy development.